Caracterização do ar ambiente de minas subterrâneas de carvão da Jazida Sul Catarinense - Bonetti, Beatriz (2017)
A characterization of the air in underground coal mines is important because it allows the issues focused on safety at work and the environment. The aim of this study was to determine the concentrations of methane (CH4) and carbon dioxide (CO2) along the ventilation system of three underground coal mines (Minas A, B and C) located in Jazida Sul Catarinense in the South CH4 is an asphyxiant and flammable gas that needs to be monitored because of its explosive risk. CO2 is a choking gas and should, like CH4, be monitored. Both are greenhouse gases (GHG). For sampling and subsequent characterization of the gases, chromatographic methods were tested and collectors were validated. The results indicated that, for storage of air samples from the mines, borosilicate bottles with butyl rubber septa and PTFE / Silicone protective cap (AV_BR) performed better. The two chromatographic methods studied the analysis of gases, each with its restrictions. The highest concentrations of CH4 (1.8%) are in areas of strong gas emanation at Mine A, below the explosive limit (5%). Therefore, exposure limits (3,900 ppm and 5,000 ppm) for CO2 were exceeded (6,086 ppm) in the emanation areas, indicating a need to increase the level of ventilation at these sites. (Mine A) as varied estimates of 173 t CH4 / year (Method 3) at 3,984 t CH4 / year (Method 1). The application of the alternative methodology (Method 3) allowed a pioneer estimation of direct CO2 emissions, indicating contributions of 27 to 77% for total GHG emissions for mines studied. Therefore, it should be emphasized that the results obtained in this study are an attempt to improve these estimates. However, to improve the accuracy of inventories, more sampling should be done covering all mines in operation in the country.